KREATIVITAS SENI GRAFIS LINOCUT DI MASA PANDEMI - Dwi Novita Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2021)
For some people, limiting activities during the pandemic actually makes them more creative, such as graphic and fine arts artists from Bali who are members of